Pregnancy-associated glycoproteins as a potential marker for diagnosis of early pregnancy in goats: A scoping reviewing - Nandini Sharma; Shiva Pratap Singh; Alok Bharadwaj; Ramachandran Natesan (Asian Pacific Journal of Reproduction, 2020)
Early diagnosis of pregnancy plays an important role to minimize reproductive losses in farm animals. There are several methods for pregnancy diagnosis like profiling of reproductive hormones (such as progesterone and estrone sulfate), but sometimes they provide false-positive results. Embryo specific pregnancy markers, which delineate the presence and viability of the embryo, are considered as perfect for pregnancy determination. Pregnancy-associated glycoproteins are distinguished as the best indicator for the determination of early pregnancy, fetal number, and birth weight of kids. Pregnancy-associated glycoproteins are structurally correlated to aspartic proteinase and are communicated in the external epithelial cell layer of the placenta. They have been found to share about half amino acid sequence identity with pepsinogen, pepsin, cathepsin D and E. Dislike different individuals from aspartic proteinase family, numerous pregnancy-associated glycoproteins appear to be latent compound as a result of amino acid substitutions in and around the catalytic site. This review is to discuss the scope and prospects of pregnancy-associated glycoproteins as a pregnancy marker in farm animals, more specifically in goats.